CORRELATION OF PRO-OXIDANT WITH ANTIOXIDANT SYSTEMS IN CASE OF COLORECTAL TUMORS - S. А. Zuikov; B. G. Borzenko; О. V. Zuikova (Сибирский онкологический журнал, 2016)
Correlation between purinenucleotides exchange and antioxidant system in patients with colorectal cancer (CC), as well as influence of key enzymes of purine decomposition on formation of active forms of oxygen were studied. During the process of study, enzymatic indicators of prooxidant system – adenosine deaminase and xanthineoxidase, as well as the level of nitric oxide were identified. Superoxidedismutase and glutathione peroxidase were the indicator of antiradical system. 22 patients aged 40–59 years with colorectal cancer of different stage were examined. A significant increase in indicators of prooxidant system in tissue homogenate of patients with CC and ambiguous changes in the activity of the antioxidant system, depending on the stage of the disease, were established. It was established that during the oxidative stress and in conditions of hypoxia, at the later stages of cancer, antioxidants may contribute to better survival ability of tumor cells and to more rapid tumor progression.